2022
DOI: 10.17275/per.22.63.9.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Animation-Based Worked Examples Supported with Augmented Reality on the Academic Achievement, Attitude and Motivation of Students towards Learning Programming

Abstract: This study examines the effect of using animation-based worked examples (ARAWEs) that are prepared using Augmented Reality (AR) technology instead of using traditional paper-based worked examples (TWEs) on the achievement, motivation, and attitude of high school students during their programming education. The research was designed through the "Nonequivalent Control Group Model", one of the quasiexperimental models. The participants consisted of second year students (N=94) who were taking the "Basics of Progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…This study found that AR and animation technology-supported STEM activities brought together more than one discipline in an interconnected way by contributing to students' knowledge in various fields and their thinking skills. Moreover, it was determined that animation-based teaching materials prepared using AR technology increase students' interest and motivation in the subject and their use in lessons that include teaching problem-solving skills, such as mathematics, physics, and chemistry in literature (Cevahir, Özdemir, & Baturay 2022). This situation may be related to the students' desire to use activities similar to those used in different lessons within the scope of the study.…”
Section: Resultsmentioning
confidence: 99%
“…This study found that AR and animation technology-supported STEM activities brought together more than one discipline in an interconnected way by contributing to students' knowledge in various fields and their thinking skills. Moreover, it was determined that animation-based teaching materials prepared using AR technology increase students' interest and motivation in the subject and their use in lessons that include teaching problem-solving skills, such as mathematics, physics, and chemistry in literature (Cevahir, Özdemir, & Baturay 2022). This situation may be related to the students' desire to use activities similar to those used in different lessons within the scope of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Cevahir et al (2022) stated that the utilisation of animation could affect students' achievement. It was found that the characteristics of animation can make a tempting process of teaching and learning.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, syntax errors—a major frustration among programming students—are completely eliminated [9, 43, 94, 140]. Other benefits of program animations include their ability to enhance students' program construction [140], support procedural programming [142], improve programming confidence and enjoyment [10], and increase overall performance [17, 18, 129, 157].…”
Section: Literature Reviewmentioning
confidence: 99%